GAMBARAN KARAKTERISTIK PASIEN ABORTUS DI PUSKESMAS KECAMATAN TERARA - Baiq Alifia Putri Prasasti (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2023)
Background: Abortion or what is more commonly called miscarriage is the death of a fetus in the womb before the gestational age reaches 20 weeks or the baby's weight is less than 500 grams, that is, before the fetus can live outside the womb independently. Based on data obtained from several Community Health Centers, it is known that in 2022 at the Rarang Health Center the number of pregnant women was 426 and 33 people experienced abortions (7.7%) while at the Terara Health Center in 2022, the number of pregnant women was 463 and who had an abortion as many as 39 people (8.4%).Purpose To find out the description of the characteristics of abortion patients at the Terara District Health Center. Methods: This research is a descriptive method using a cross sectional approach. The population is all pregnant women who have had an abortion at the Terara District Health Center, which consists of: the Working Area of the Rarang Health Center and the Working Area of the Terara Health Center from 2021 to July 2022 as many as 197 people. The sampling technique used was stratified random sampling so that a total sample of 132 people was obtained. Data collection through the register. Results: The results showed that most of the abortion patients had anemia as many as 85 people and seen as a whole the majority (79.5%) of the abortion patients had at least one risk factor while patients who did not have risk factors were (20.5%). Conclusion: Age, parity, distance between pregnancies, history of abortion and anemia are factors that can affect the occurrence of abortion in pregnant women